An adaptive tunable Janus emitter with controllable unidirectional emission for thermal management in enclosed spaces - Feifei Ren; Huan Guan; Hang Wei; Jinxin Gu; Shuhui Liang; Chenchen Geng; Jianjun Li; Shuliang Dou; Yao Li (Next Energy, 2023)
The heating and cooling of enclosure space consume a large part of the global energy and contribute to the rise of extreme weather and the greenhouse effect. The radiative cooling and heating function by emitting infrared waves is a passive thermal management strategy, yet most of the research ignored the effect of inner radiance on the object temperature in enclosed spaces. Herein, a tunable Janus emitter with two types of multilayer configuration consisting of VO2/SiO2/ITO was designed and achieved controllable unidirectional emission for thermal management of enclosed spaces. The Fabry-Perot cavity helps create asymmetrical infrared emission on the separate sides, as well as tunable emissions are produced on both sides when the metal-insulating transition of VO2 occurs. This design results in not only remarkable thermal management within enclosed spaces, but also controllable heat insulation and release ability for outdoor spaces. This work may provide new strategies for energy saving, personal thermal management, and other facilities.